The comparison of additional extracts of merah, emprit, and gajah ginger towards characteristics of yogurt - Dwi Cahyani Anna; Aji Handoko Yoga (BIO Web of Conferences)
Yogurt is a solution for people who cannot digest lactose (lactose intolerance) and can be innovated by adding various ginger extracts. This research aims to compare the characteristics of yogurt with the addition of various ginger extracts and determine the best variety of ginger extract. The experimental design used a Randomized Block Design. Data were analysed using ANOVA and continued with the Honestly Significant Difference test at a significance level of 5%. The testing parameters are protein, fat, antioxidant activity, acid total, total Lactic Acid Bacteria, and organoleptic. The results showed that by adding merah ginger extract, the protein of yogurt decreased (sample M.3%), besides that the fat and antioxidant activity (sample M.3%) were the lowest compared to other treatments. The addition of emprit ginger extract makes yogurt have the highest protein, fat, and antioxidant activity (sample E.1 & 5%). The addition of gajah ginger extract resulted in the highest total lactic acid bacteria (sample G.1 and 3%), while the protein, fat, acid total, and antioxidant activity tended to be low. The best variety of ginger extract for the quality of the final yogurt product is the addition of 1% emprit ginger (sample E.1%) and 3% gajah ginger (sample G.3%).